Dualistic Passion for Work and Its Impact on Career Outcomes: Scale Validation and Nomological Network. (November 2018) - Lajom, Jennifer Ann L.; Amarnani, Rajiv K.; Restubog, Simon Lloyd D.; Bordia, Prashant; Tang, Robert L.
Drawing on the dualistic model of passion, we conducted a construct validation of the passion for work scale across four samples of employees and students. Specifically, we tested the two-factor structure of the model and examined the convergent, discriminant, and criterion validity of passion for work against conceptually similar work motivation and career-relevant constructs. Findings support the duality of the passion for work (i.e., harmonious and obsessive), its uniqueness as a motivational work construct, and its consequences on career-related outcomes. The findings also contribute to the increasing breadth of the passion literature across various contexts and its consequences for one's work and career experiences.